Assessment of Treatment Outcomes and Associated Factors Among Pediatric Patients With Burkitt Lymphoma at Kenyatta National Hospital - Divya Kumari Toor; Amsalu Degu; Peter N. Karimi (Cancer Reports)
ABSTRACT Background In developing countries, the treatment outcomes of Burkitt lymphoma are poor due to the poorly equipped healthcare systems. In addition, there is limited comprehensive data within the African continent, including Kenya, about the outcomes of treatment for this cancer. Aims To assess treatment outcomes and variables associated with an increased risk of death from disease progression or treatment‐related toxicities among Burkitt lymphoma pediatric patients at the Kenyatta National Hospital (KNH). Methods and Results A retrospective one‐arm cohort study was conducted to examine the treatment outcomes of pediatric patients with Burkitt lymphoma. All eligible Burkitt lymphoma pediatric patients treated between January 1, 2016 and December 31, 2022 were included. The patients were retrospectively monitored from the initial cancer diagnosis until either death or the last follow‐up appointment visit in the facility. Data analysis of factors associated with treatment and disease progression‐related death was carried out using the SPSS version 29.0 software. Kaplan–Meier survival and Cox regression analyses were employed to determine the survival time and predictors of mortality, respectively. The median age of the patients at diagnosis was 6 years (range: 3–13 years). The majority of patients were diagnosed with Stage IV disease accounting for 46.7% of all patients. Of the 75 patients studied, 24% (18) of them were died. The 5‐year overall survival rate was 70%, and most patients had stable disease during the follow‐up period. Patients with Stage IV disease who were treated with full‐fuse chemotherapy were 19.2 (AHR = 19.2, 95% CI = 5.2–48.5, p < 0.001) and 7.4 times (AHR = 7.4, 95% CI = 2.2–19.9, p = 0.003) more hazard of dying as compared to patients without metastasis and received a combination of radiation and reduced‐dose chemotherapy, respectively. However, the age, gender, stage of cancer, histological type of cancer, and co‐morbidity were not significant predictors of survival. Because of the retrospective nature of the study design, the data accuracy relied on the proper documentation of medical records in the study setting. Conclusion The 5‐year overall survival rate among pediatric burkitt's lymphoma patients was above average as compared to other African countries. Most patients had reduced tumor size and stable disease during the follow‐up period. Metastases and full‐fuse chemotherapy were significant predictors of mortality.